Corporate strategies for Radio Veritas Global Broadcasting System Inc. - Alejo, Marcelino J., Jr. (Animo Repository, 1998)
This paper will strive to create strategies for Radio Veritas Global Broadcasting System Inc. in an industry affected by changing technological, social and economic environment. The media industry is in a state of flux as business enterprises have acquired the power to communicate directly to consumers via the Internet. The study will examine how the company should react in the light of these changes. The environment module discusses the factors that will affect the company strategies. The five forces model of Michael Porter was used to analyze the industry of the competition in the environment and its effect on the profitability of the industry. Several opportunities in the media industry were observe. These include the opportunity to expand audience base in areas that have not yet been fully penetrated by media firms, the shift in the population towards broadcast media and away from the print media, and the opportunity for media to create additional revenues via the Internet. On the other hand, the following factors were found to be threats that may affect the industry. First, there is a potential decline in profits due to the rise in the prices of imported equipment brought about the currency crisis. Second, potential decline in profits may also result from advertisers may opt to create their own web sites instead of acquiring the services of media firms. The corporate module focuses on the company, specifically the strength and weaknesses determined according to the results of the financial analysis and value chain activities. Results show that Radio Verita's strengths are its ability to reach more people with its broadcast equipment, ability to pioneer new programs/modules due to creative personnel. In addition, its tie up with the Catholic Media Network allows Radio Veritas to provide bonus spots to advertisers. On the other hand, DZRV âs weaknesses are follows: inability to provide the necessary training and support for account executives, inability of personnel to specialize in one function due to disorder in organizational hierarchy, failure to maintain programs with a long life span due to the absence of planning, and low current ratio of 1.293. Fixed asset turnover shows that sales are not enough to recover costs of fixed assets. Moreover, there is the inability to efficiently collect outstanding debts as seen from the average collection period of 14 days. The strategy module discusses how the company can utilize its strengths and weaknesses to take advantage of the opportunities and ward of threats. Based on the analysis, the following strategies were formulated. These include linking DZRV to CMN affiliate stations by allowing real-time broadcasting of DZRV programs, developing an in-house sales force via intensive recruitment and training, redefining the organizational setup to eliminate multiplicity of functions and improve efficiency, establishing R&D for program development, and most importantly, creating an audience base in rural areas via programs that cater to the appropriate listeners. The strategies were designed to differentiate Radio Veritas from other competing radio stations in the country. The implementation module highlights the importance of examining the organizational effectiveness of the company before strategies are implemented. McKinsey 7-S framework is used to examine the organization capabilities in strategy implementation. Finally, strategy-implementing tasks were developed.